2019
DOI: 10.7547/17-025
|View full text |Cite
|
Sign up to set email alerts
|

Does Immobilization Affect Braking Time?

Abstract: Background: Despite the importance to patients of driving, no well-established guideline exists to help either the patient or the physician determine when it is safe for the patient to return to driving. Previous studies have recommended 6 weeks postoperatively before patients can return to driving safely. Several scientific studies have found the nationally recommended safe brake time standard to be 1.25 sec (1,250 msec), looking at brake reaction time (BRT) in all types of patients, surgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…In total, 68 studies were identified meeting our study aims and inclusion criteria for both upper and lower extremity procedures ( Fig. 1 , Table 1 , Supplementary Tables 1 and 2) ( 1 , 14 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ). There was a wide variation in procedures performed and sample size, the study methodology, and measurements obtained.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In total, 68 studies were identified meeting our study aims and inclusion criteria for both upper and lower extremity procedures ( Fig. 1 , Table 1 , Supplementary Tables 1 and 2) ( 1 , 14 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ). There was a wide variation in procedures performed and sample size, the study methodology, and measurements obtained.…”
Section: Resultsmentioning
confidence: 99%
“…There were 36 lower extremity studies included in the review ( 4 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ) A total of 1021 patients were assessed, with 1006 having right-sided procedures and 15 left-sided procedures. The summary of these data is presented in Supplementary Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations